Discover the answers you need at Westonci.ca, a dynamic Q&A platform where knowledge is shared freely by a community of experts. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

3y=-2x-19 -5x-3y=-2

Sagot :

3y=-2x-19 -5x-3y=-2-5x - (-2x - 19) = -2
-5x + 2x + 19 = -2
-3x = -21
x = 7

3y = -2(7) - 19
3y = -14 - 19
3y = 33
y = 11
3y = -2x - 19 ⇒   2x +  3y = -19
-5x - 3y = -2  ⇒ -5x -   3y = -2
                                   -3x = -17
                                    -3      -3
                                      x = 5²/₃
                           -5x - 3y = -2
                     -5(5²/₃) - 3y = -2
                       -28¹/₃ - 3y = -2
                     + 28¹/₃          + 28¹/₃
                                  -3y = 26¹/₃
                                   -3      -3
                                     y = -8⁷/₉
                               (x, y) = (5²/₃, -8⁷/₉)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.